Satisfaction level of Postnatal Mothers about Antenatal Care in Jumla, Nepal - Bhattarai, Saraswoti Kumari Gautam; Pahadi, Nirmala Kumari; Chaulagain, Sandhya; Mahat, Shrijana; Panta, Prem Prasad; Panth, Asha; Gautam, Kanchan; Khadka, Rabin (Journal of Karnali Academy of Health Sciences, 2022)
Background: Client satisfaction is essential for improvement of quality of antenatal care and to increase service utilization. Therefore, this article aimed to assess the level of satisfaction of postnatal mothers About antenatal care services in Chandannath Municipality of Jumla, Nepal. Methods: The descriptive cross sectional study design was conducted to assess the level of satisfaction of postnatal mothers about antenatal care services in Chandannath Municipality of Jumla, Nepal. The study population was postnatal mothers within one year of child birth who came in maternal and child health (MCH) clinic for the immunization of their baby. Total 367 postnatal mothers within one year of childbirth were recruited by adopting simple random sampling technique, and face to face interview was done by using Likert scale to collect the data. Data analysis was done by using descriptive statistics. Results: Regarding the satisfaction on antenatal care received by postnatal mothers on different aspects, majority were satisfied with the information received regarding prenatal test and procedures (68.1%), and antenatal guidance/counseling on preparation for child birth (61.3%). Similarly, more than half were satisfied with time given to answer their questions (57.5%). About approachability, less than half (45.8%) were dissatisfied because providers were hurried during antenatal visit. Concerning the availability; majority (68.9%) were satisfied because they got in touch with care providers. Likewise, majority of mothers were satisfied with respect (67.0%) and support (64.0%) from providers. Regarding the satisfaction level on antenatal care received by postnatal mother, majority of them (71.4%) were satisfied and 28.6% were dissatisfied from antenatal care they received. Conclusion: The facility based study showed that the majority of postnatal mothers were satisfied and one third were not satisfied from antenatal care. So community based study should be conducted to find out the actual satisfaction level.